PEMASTIAN VALIDITAS PENGUJIAN KADAR SENG SECARA KOMPLEKSOMETRI TERHADAP MODIFIKASI TEKNIK PREPARASI DALAM KONSENTRAT SENG SULFIDA - Ekawandi, Fanny Rahman; Hardian, Arie; Herawati; Mapiliandari, Inda (Jurnal Teknologi Mineral dan Batubara, 2023)
Sphalerite is one of the sulfide ore minerals that serves as the raw material for zinc sulfide concentrate (ZnS). Sphalerite in nature needs to be processed through a concentration process to become a high-value ZnS concentrate. The determination of zinc (Zn) content in the ZnS concentrate is carried out using complexometric methods, referring to the modified ISO 13658:2000 method in the preparation stage. In this research, the validity of the test results was conducted using several parameters, including precision testing (repeatability and reproducibility), accuracy (recovery and test result comparison with CRM value), and measurement of relative uncertainty in Zn content determination in ZnS concentrate using the modified ISO 13658:2000 method, it is conducted by two analysts. Certified reference material (CRM) O354 with a Zn content range of (49,30±2,46)% was used as a sample in this research. Zinc content in CRM O354 by Analyst X obtained 49.30% with RSD=0.37% and range of Recovery=(99.5-100.6)%, while Analyst Y obtained 49.03% with RSD=0.64% and range of Recovery=(98.1-99.9)%. Mean of results of the determination of Analyst X and Analyst Y is 49.13% with an uncertainty expanded by 1.90% so, Zn content is obtained at (49,13±1,90)% and the relative uncertainty is obtained at 3.87%. The minimum criteria for precision testing in terms of repeatability are RSD<2/3 CV Horwitz, and for reproducibility (F-test), Ftest<Ftable, for accuracy testing in terms of Recovery=(98-102)%, inter-analyst comparison, and test result comparison with CRM value (t-test), ttest<ttable as well as the minimum criteria for measurement of relative uncertainty<5%. Therefore, the test results of the modified ISO 13658:2000 method for Zn determination in ZnS concentrate have fulfilled all the validity parameters of the test results.